(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The significance of agriculture in economic development of any nation, rich or poor is borne out by the way that it is the essential division of the economy, which gives the fundamental fixings important to the presence of humankind and likewise gives most of the raw materials which when changed into completed items fill in as essential necessities of mankind. In India agriculture is the biggest segment of economic action. It gives food and raw materials as well as work to an exceptionally expansive extent of the populace. It has dependably remained the most imperative economic division of Indian economy. It has likewise been the wellspring of raw materials to our driving ventures, for example, sugar, cotton and jute, textiles, hydro-created oils, food items, cleanser and other agro-based enterprises which together record for 50 of the salary produced in the assembling segment of India. There was a colossal increment in wheat creation in the nation in seventies which introduced the Green Revolution in the nation. In this article we analyzed season wise unemployment and employment on the basis of three seasons.